2018
DOI: 10.1002/adom.201800832
|View full text |Cite
|
Sign up to set email alerts
|

Gate‐Tunable Photoresponse Time in Black Phosphorus–MoS2 Heterojunctions

Abstract: Gate‐/wavelength‐dependent scanning photocurrent measurements of black phosphorous (BP)–MoS2 heterojunctions have shown that the Schottky barrier at the MoS2–metal interface plays an important role in the photoresponse dynamics of the heterojunction. When the Fermi level is close to the conduction band of MoS2, photoexcited carriers can tunnel through the narrow depletion region at the MoS2–metal interface, leading to a short response time of 13 µs regardless of the incident laser wavelength. This response spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…The maximum photocurrent is observed at V g = 25 V ( Figure S8) and the corresponding photoresponsivity is calculated up to 8500 mA/W with V d = 0.7 V. Figure 3D summarizes the relationship between the photoresponsivity and the wavelength. Our device can exhibit sufficiently high sensitivity in visible and near-IR wavelength, and the obtained results are better than that of the most reported photodetectors based on 2D materials, as shown in Table S1 [30,31]. It is also worth mentioning that the properties are also comparable to that of most reported photodetectors based on hybrid perovskite [32][33][34][35].…”
Section: Resultssupporting
confidence: 52%
“…The maximum photocurrent is observed at V g = 25 V ( Figure S8) and the corresponding photoresponsivity is calculated up to 8500 mA/W with V d = 0.7 V. Figure 3D summarizes the relationship between the photoresponsivity and the wavelength. Our device can exhibit sufficiently high sensitivity in visible and near-IR wavelength, and the obtained results are better than that of the most reported photodetectors based on 2D materials, as shown in Table S1 [30,31]. It is also worth mentioning that the properties are also comparable to that of most reported photodetectors based on hybrid perovskite [32][33][34][35].…”
Section: Resultssupporting
confidence: 52%
“…The photocurrent signals can be plotted versus time (Figure3b), where the rise and decay time constants of the signals are extracted with a single exponential fitting function. Under zero bias, where the MoSe 2 −MoS 2 heterojunction features sizable photocurrent signals, the rise and decay time constants are ∼18 μs and ∼16 μs (Figure3c), respectively, which are three orders of magnitude faster than previous 2D MoSe 2 -based phototransistors 4,10,38,39,52−57 and is comparable with other 2D TMDC phototransistors 29,58. Interestingly, the rise and decay time constants for the MoSe 2 −WSe 2 heterojunction under −30 mV bias are ∼ 17 μs (Figure3d), which are similar to those of the MoSe 2 −MoS 2 heterojunction.…”
mentioning
confidence: 53%
“…These characteristics naturally facilitate the incorporation of TMDCs into electronic and optoelectronic devices, such as field-effect transistors (FETs), photodetectors, photovoltaic cells, , and many other applications . While some device improvements are achieved through the use of different TMDC channels, other works suggest that 2D heterostructures will also enhance device performance. Therefore, substantial efforts have been expended in understanding the underlying mechanisms within TMDC heterostructures and their commercial synthesis. For example, it has been shown that heterostructures consisting of different atomically thin materials like black phosphorus, graphene, and TMDCs can result in devices with improved optoelectronic properties, such as increased mobility and reduced response times while foregoing thermal stability in the former examples. , Moreover, heterostructures formed between heavily doped TMDCs and undoped TMDCs display similar enhancements whilst further reducing Schottky barrier heights, resulting in low-resistance ohmic contacts . Such improvements are imperative to attain high-performance optoelectronic devices which allow for the ultrafast movement of information, a highly sought after property of commercial and academic endeavors alike …”
Section: Introductionmentioning
confidence: 99%
“…Contrary to above physical contact scheme, epitaxial growth results in a direct bonding between 0D and 2D materials without any linker ligand for carrier transfer. [17,[20][21][22] In this study, we propose a new strategy for the fabrication of 0D/2D heterostructure, where the PbS nanocrystals (NCs) are epitaxially grown from PbI 2 nanosheet templates by a wetchemical sulfuration process. Due to their large size ≈10 nm, the IR absorption wavelength range of PbS NCs extends up to 2000 nm.…”
Section: Introductionmentioning
confidence: 99%